Detection of antimicrobial resistance among Enterococci isolates by vitek system - REENA RAJAN; C.AMIRTHA; K.M.MOHANA SOUNDARAM; V.ANANDI (International Journal of Pharma and Bio Sciences, 2017)
The clinical significance of Enterococci is directly related to its antimicrobial resistance. Enterococci are inherently resistant to many antibiotics and can acquire resistance by mutation, or acquisition of plasmids or transposons. Fifty six Enterococci isolates from various clinical samples were identified to species level and their antimicrobial sensitivity pattern was determined by conventional method and Vitek system. Forty four (78.57%) were Enterococcus faecalis, nine (16.07%) were Enterococcus faecium and, three (5.36%) were identified as Enterococcus avium. Of the total isolates, 11(19.64%) were resistant to penicillin (MIC ≥16µg/ml). Among E.faecium isolates, 4(44.44%) were with MIC of 16 µg/ml for vancomycin and one isolate was resistant to both vancomycin (MIC ≥ 32µg/ml) and teicoplanin (MIC ≥32µg/ml). Out of 49 isolates from urine, 39(79.59%) were sensitive to nitrofurantoin (MIC ≤ 16µg/ml). The antimicrobial susceptibility testing by Vitek was concordant with the results of disk diffusion for penicillin and vancomycin. Two minor errors (discrepancy between results of reference method and test method, that differed by one interpretation category) were detected for erythromycin and nitrofurantoin and one minor error was detected for ciprofloxacin. Five very major errors (Isolates resistant by reference method, identified as susceptible by test method) were detected in teicoplanin resistance. Vitek analyser provides Enterococcus susceptibility data, significantly faster than conventional methods used in diagnostic laboratory.